2022
DOI: 10.1177/21674795211063537
|View full text |Cite
|
Sign up to set email alerts
|

“Willpower knows no obstacles”: Examining Neoliberal Postfeminist Messaging in Nike’s Transnational Advertisements for Women

Abstract: Nike, a US-headquartered transnational corporation lauded for its putatively empowering women-centered advertisements, frequently releases nationally/regionally focused advertisements depicting women determinedly engaging in physical activity and, in doing so, overcoming gendered barriers and stigmas. Indeed, the global ubiquity of the empowered (Nike-clad) woman illustrates Nike’s role in advancing women’s empowerment, both in the US and globally. Universalizing “just do it” beyond geographical borders, Nike’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…This results in one’s appearance becoming the ‘vehicle to female recognition and validation’ (p. 108), and on the flip side, also disapproval and rejection when women are unable or unwilling to conform to such consumer driven ideals. Research has shown how this ‘postfeminist gaze’, as well as the broader ideas within postfeminism and neoliberalism, are exemplified in the activewear industry (Brice and Thorpe, 2021a; Lavrence and Lozanski, 2014; Nash, 2016; Posbergh et al, 2022). In particular, activewear clothing has been described by some as a ‘tracking device on the yogic body’ (Luna Mora and Berry, 2021: 417) showing the bumps, the curves, and the fat on a body and providing an avenue for women to judge other women’s attempts to modify and transform their physique.…”
Section: Conceptual Framing and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in one’s appearance becoming the ‘vehicle to female recognition and validation’ (p. 108), and on the flip side, also disapproval and rejection when women are unable or unwilling to conform to such consumer driven ideals. Research has shown how this ‘postfeminist gaze’, as well as the broader ideas within postfeminism and neoliberalism, are exemplified in the activewear industry (Brice and Thorpe, 2021a; Lavrence and Lozanski, 2014; Nash, 2016; Posbergh et al, 2022). In particular, activewear clothing has been described by some as a ‘tracking device on the yogic body’ (Luna Mora and Berry, 2021: 417) showing the bumps, the curves, and the fat on a body and providing an avenue for women to judge other women’s attempts to modify and transform their physique.…”
Section: Conceptual Framing and Literature Reviewmentioning
confidence: 99%
“…Such exclusionary practices have been seen across the fitness industry where magazines, social media, fitness manuals, exercise regimes, and broader fitness discourses work as 'increasingly important tool [s] for shaping the body into a narrowly defined, singular feminine ideal' (Markula and Kennedy, 2011: 2). This has been true in the activewear sector, as well, which not only promotes ideals of empowerment, choice, and freedom in line with postfeminist values (Horton et al, 2016;Nash, 2016;Posbergh et al, 2022), but also primarily features 'the white middle-class (heterosexual) female body' (Nash, 2016: 224). For example, in their analysis of the Instagram accounts of lululemon and Aloyoga, Luna Mora and Berry (2021) show how the company mainly posts images of White, youthful, slim yoga models which become associated 'with higher and better morals' (p. 406).…”
Section: Conceptual Framing and Literature Reviewmentioning
confidence: 99%
“…Featuring 24 teams, the tournament culminated in a 2-0 U.S. win over the Netherlands in front of 57,900 spectators (FIFA Women's World Cup France 2019 Match Report). A record 1.12 billion people watched this tournament on television, double the viewership from 2015 (FIFA The Vision, 2020-2023. In its reach through media, the FIFA Women's World Cup thus ranks highly among women's sport mega-events, these defined as "large-scale cultural (including commercial and sporting) events, which have a dramatic character, mass popular appeal and international significance" (Roche, 2000, p. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Women's sporting events, including sport mega-events, are commonly framed through a discourse of the empowerment of girls and women (Bob & Swart, 2010;Brice & Andrews, 2019;McLachlan, 2019;Pavlidis et al, 2022). The elastic concept of "empowerment" is often defined through a neoliberal postfeminist lens that emphasizes equality achieved and women's personal responsibility for navigating systemic sexism, especially though assertiveness and competitiveness on a supposedly level playing field (Brice & Andrews, 2019;Dashper, 2022;Desjardins, 2021;Posbergh et al, 2023). For example, Toffoletti (2017) finds in images of supporters attending the 2015 Women's World Cup a focus on the empowered "can-do" girl "who is capable, competent and embodies the potential and capacity of young women everywhere" with no recognition of systemic obstacles to success (p. 124).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation